Congestion and Diuretic Resistance in Acute or Worsening Heart Failure - Ingibjörg Kristjánsdóttir; Tonje Thorvaldsen; Lars H Lund (Cardiac Failure Review)
Hospitalisation for acute heart failure (AHF) is associated with high mortality and high rehospitalisation rates. In the absence of evidence-based therapy, treatment is aimed at stabilisation and symptom relief. The majority of AHF patients have signs and symptoms of fluid overload, and, therefore, decongestion is the number one treatment goal. Diuretics are the cornerstone of therapy in AHF, but the treatment effect is challenged by diuretic resistance and poor diuretic response throughout the spectrum of chronic to worsening to acute to post-worsening HF. Adequate dosing and monitoring and evaluation of diuretic effect are important for treatment success. Residual congestion at discharge is a strong predictor of worse outcomes. Therefore, achieving euvolaemia is crucial despite transient worsening renal function.